Obstructive Sleep Apnea in Individuals with Down Syndrome: A Meta-Analytic Literature Review - Ridore Sharanah; Debbarma Swarnalata; Nazir Racha; S. Bennett David; Sedky Karim (Journal of Sleep And Sleep Disorder Research, 2017)
Objective: Individuals diagnosed with Down syndrome (DS) are predisposed to obstructive sleep apnea (OSA). The aim of this study is to assess the prevalence of OSA and factors associated with OSA in this population. Study Design: Systematic literature review and meta-analysis. Methods: Studies of DS and OSA in the English language through May 2017 were reviewed. Since parental report of symptoms has limited validity related to the diagnosis of OSA, only studies using in laboratory polysomnography to diagnose OSA were included. Results: Twenty three studies examining OSA among 1,469 people with DS were found. Among ten studies using community referred samples, 71.5% of people with DS had OSA, compared to 69.6% in referred community samples suspected of having respiratory events. There was an inverse relationship between apnea hypopnea index (AHI) cutoffs and OSA prevalence as higher cutoffs were associated with somewhat lower prevalence. Examining age groups, adults had a higher prevalence of OSA (90.0%) compared to infants (66.5%) and children between 2-21 years of age (69.9%). Oxygen desaturation and gender did not affect prevalence. Although surgery had less effect on successfully treating OSA among DS individuals compared to those without DS in prior studies, lingual tonsillectomy had the greatest effect (mean AHI decrease of 9.0). Conclusion: OSA appears to occur frequently in children and adults with DS. Untreated, OSA may contribute to health problems and premature death, highlighting the potential importance of identifying OSA among people with DS. Even after traditional surgeries (i.e., adenotonsillectomy, tonsillectomy, adenoidectomy), repeating PSG is highly recommended as residual OSA can persist
Keywords: Down Syndrome